Diseño de un modelo de gestión de Responsabilidad Social Empresarial, en el área de Relaciones Comunitarias de la empresa BGP ECUADOR CO S.A., de la ciudad de Quito, período 2014, bajo estándares ISO 26000. - Real Lascano, Tania Gisela (2014)
This research is directed to the analysis of Social Business Responsibility, which is part of discussion in different sectors of society, according with the thematic is the roll’s company responsibility to have a right arrangement of social practices. From that previous analysis comes up our mind the necessity to develop the follow research; looking for status and leadership of the company BGP Ecuador CO S.A., focus on Social business responsibility in the area of community relations, inside of hydrocarbon industry. The previous diagnostic has taken us to create a management model based on Social Business Responsibility; applied in the area of community relations of the company BGP Ecuador CO S.A., it will be an easy applicable process whiting the organization, which guarantees the personal development of its human resource and the company’s growth through social responsible acts. CLUE WORDS: Social Business Responsibility, community relations, politic and practice business social responsibility, business etic, management model, social balance.